Prediction of Preterm Birth by Second Trimester Transvaginal Ultrasound Measurement of Cervical Length. A Prospective Observational Study at a Tertiary Care Hospital - Robina Kousar; Bushra Iftikhar; Fatima Sharif Khan; Rehana Kousar; Fatima Mahmood; Huma Shahzadi (Life and Science)
Objective: To determine the predictive value of second-trimester transvaginal ultrasound measurement of cervical length for preterm birth. Study Design: Prospective observational study. Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology, Pak Emirates Military Hospital (PEMH), Rawalpindi, Pakistan, a tertiary care facility from April 2023 to September 2023. Methods: After obtaining written informed consent, 132 pregnant women who met the selection criteria were enrolled. All patients underwent transvaginal ultrasonographic evaluation during the 20th to 24th week. A consultant gynaecologist assessed cervical length three times. The smallest measurement was noted down, and it was further confirmed by a consultant radiologist. All patients were followed up until delivery, and preterm birth was assessed; findings were analyzed statistically. No intervention was done during this study. Results: The mean age of the patients was 28.5 ± 3.91 years. Cervical shortening (<2.5cm) was seen in 24 (18.2%) patients. Overall, pre-term birth occurred in 27 (20.5%) patients. In patients with cervical shortening, preterm birth occurred in 16 (66.7%) patients. A statistically significant relation existed between cervical shortening and preterm birth (P=0.000). The sensitivity, specificity, PPV, and NPV of cervical shortening for determining preterm birth were 59%, 92.5%, 66.5%, and 89.9%, respectively. The Chi-square value was 38.47, which shows a statistically significant relationship between cervical shortening and preterm birth. In other words, cervical is strongly associated with a higher risk of preterm birth in this population. Conclusion: Cervical length measured by TVS during the second trimester had a moderately high predictive value and specificity for predicting preterm birth.